Employer Support for Innovative Work and Employees' Job Satisfaction and Job‐related Stress. Issue 4 (3rd October 2014) - Raykov, Milosh
Abstract : Employer Support for Innovative Work and Employees' Job Satisfaction and Job‐related Stress: Milosh RAYKOV. Faculty of Education, University of Malta, Malta— Objectives: There are high levels of global and national underemployment, but limited information is available on the impact of this phenomenon on the quality of employees' working lives. This study examines the relations among perceived employer support for creative work, different forms of underemployment and employee quality of life, including job satisfaction, perceived job security and job satisfaction. Methods: The study was performed using cross‐sectional data from the Canadian 2010 Work and Lifelong Learning Survey (WALL), which included 1, 042 randomly selected currently employed participants between the ages of 18 and 64 years of age. Results: The study found a significant inverse association between employer support for innovative work and different forms of underemployment. It also suggested a strong relationship between support for such work and participation in work‐related informal learning. The results from this study confirmed the hypothesis that employer support for creative work is significantly associated with the quality of employees' working lives, as manifested through increased job security and job satisfaction. Employees experiencing greater support for workplace creativity report less job‐related stress. The present study identified relatively low employer support for creative work and significant differences in the perception of support among managers and workers. Conclusions: The results of this study indicate that employer support for innovative work can mitigate significant underutilization of employee knowledge and skills. Such support can contribute to the reduction of job‐related stress, increased job satisfaction and perceived job security. This kind of support can also improve the quality of life of employees and facilitate creativity and overall organizational and social development.